In vitro evaluation of influence of salivary contamination on the dentin bond strength of one-bottle adhesive systems - Suryakumari, Nujella B. P. (Medknow Publications Pvt Ltd, 2011)
AIM: To evaluate the effect of salivary contamination on the bond strength of one-bottle adhesive systems — (the V generation) at various stages during the bonding procedure and to investigate the effect of the contaminant removing treatments on the recovery of bond strengths. MATERIALS AND METHODS: In this study the V generation one-bottle system — (Adper Single Bond) was tested. Fifty caries-free human molars with flat dentin surfaces were randomly divided into five groups of ten teeth each: Group I had 15 second etching with 35% Ortho Phosphoric acid, 15 second rinse and blot dried (Uncontaminated); Group II contaminated and blot dried; Group III contaminated and completely dried; Group IV contaminated, washed, blot dried; Group V contaminated, retched washed, and blot dried. The bonding agent was applied and resin composite (Z-100 3M ESPE) was bonded to the treated surfaces using the Teflon mold. The specimens in each group were then subjected to shear bond strength testing in an Instron Universal testing machine at a crosshead speed of 1 mm / minute and the data were subjected to one way ANOVA for comparison among the groups (P<0.05). RESULTS: There was a significant difference between the group that was dried with strong oil-free air after contamination (Group III) and the other groups. When the etched surface was contaminated by saliva, there was no statistical difference between the just blot dry, wash, or the re-etching groups (Groups II, IV, V) if the dentin surface was kept wet before priming. When the etched dentin surface was dried (Group III) the shear bond strength decreased considerably. CONCLUSION: The bond strengths to the tooth structure of the recent dentin bonding agents are less sensitive to common forms of contamination than assumed. Re-etching without additional mechanical preparation is sufficient to provide or achieve the expected bond strength.